142k views
4 votes
For all values of x, which expression is equivalent to 9(2x+9)+2(2x+9)

User FanManPro
by
5.2k points

2 Answers

4 votes

Here's two ways you can solve this exercise: you can expand the multiplications and sum like terms:


9(2x+9)+2(2x+9) = 18x+81+4x+18 = 22x+99

Or you can factor the parenthesis:


9(2x+9)+2(2x+9) = (2x+9)(9+2) = 11(2x+9) = 22x+99

User DHW
by
6.0k points
1 vote

Answer:

22x + 99

Explanation:

Given

9(2x + 9) + 2(2x +9) ← factor out (2x + 9) from each term

= (2x + 9)(9 + 2)

= 11(2x + 9) ← distribute parenthesis

= 22x + 99

User Mirna
by
5.8k points